2010
DOI: 10.1364/ao.49.005583
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive-optics-based sensor as a tool for detection of biocompatibility of titanium and titanium-doped hydrocarbon samples

Abstract: Adsorption of the elongated human plasma fibrinogen (HPF) and globular human serum albumin molecules on a titanium-based surface is monitored by analyzing permittivity and optical roughness of protein-modified surfaces by using a diffractive optical element (DOE)-based sensor and variable angle spectro-ellipsometry (VASE). Both DOE and VASE confirmed that fibrinogen forms a thicker and more packed surface adlayer compared to a more porous and weakly adsorbed albumin adlayer. A linear relation of the permittivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The visible-range photons are used in optical guide applications, such as optical waveguide light mode spectroscopy (OWLS) 3 and ellipsometry. 3,8,13,27 Lastly, there are methods, such as voltammetry 23,28À32 and electrochemical impedance spectroscopy (EIS), 31À35 which both sense electric charges passing through an interface system.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visible-range photons are used in optical guide applications, such as optical waveguide light mode spectroscopy (OWLS) 3 and ellipsometry. 3,8,13,27 Lastly, there are methods, such as voltammetry 23,28À32 and electrochemical impedance spectroscopy (EIS), 31À35 which both sense electric charges passing through an interface system.…”
Section: ' Introductionmentioning
confidence: 99%
“…The n pk and the m pk are the respective pixel dimension of each of the 16 peaks (pk) in the DOE image. In general, the optical roughness (R opt ) changes in the investigated surfaces can be determined with an accuracy of 0.2 nm, 8,13 which is the detection limit of this onearm interferometer and offers reasonable sensitivity in the detection of biomolecules. Gloss (G), measured in gloss units (GU), is a standard measure for optical characterization of a surface.…”
Section: ' Introductionmentioning
confidence: 99%
“…The structure and composition of the adsorbed protein layer determine the type and extent of the subsequent biological reactions, such as activation of coagulation and immune response and osseointegration (Nygren et al, 1997). Thus, the initially adsorbed protein layer is a factor determining the biocompatibility (Cai et al, 2006;Galli et al, 2001;Garguilo et al, 2004;Hemmersam et al, 2005;Kidoaki & Matsuda, 1999;Ma et al, 2007;Rouahi et al, 2006;Van De Keere et al, 2008;Wang et al, 2003), and also in recent years interest has been focused to preparation of hydrocarbons doped with Ti and used different methods to analyzing of biocompatibility for important proteins (Choukourov et al, 2008;Grinevich et al, 2009;Silvennoinen, Hason, Vetterl, Penttinen, Silvennoinen, Myller, Cernochova, Bartakova, Prachar & Cvrcek, 2010;Silvennoinen, Vetterl, Hason, Tuononen, Silvennoinen, Myller, Cvrcek, Vanek & Prachar, 2008). The production and application of doped titanium surfaces are under intensive research, and the results have shown the positive views on the adaptation of these materials as a biomaterial, as equal or even better than the bulk titanium.…”
Section: Introductionmentioning
confidence: 99%
“…DOE sensor is a non-contact optical method, in detection of biomolecules, which can sense changes on the measured biosurface as well as changes in the surface itself. (Silvennoinen, Hason, Vetterl, Penttinen, Silvennoinen, Myller, Cernochova, Bartakova, Prachar & Cvrcek, 2010;Silvennoinen, Peiponen & Myller, 2008;Silvennoinen, Vetterl, Hason, Silvennoinen, Myller, Vanek & Cvrcek, 2010;Silvennoinen, Vetterl, Hason, Tuononen, Silvennoinen, Myller, Cvrcek, Vanek & Prachar, 2008) HPF protein molecules adsorb stronger on the titanium surface, which is treated by polishing and etching, than at the surface treated only by polishing due to an increase of surface area caused by etching and thus increase the interactions caused by van der Waals forces (Parsegian, 2005;Silvennoinen, Hason, Vetterl, Penttinen, Silvennoinen, Myller, Cernochova, Bartakova, Prachar & Cvrcek, 2010;Silvennoinen, Vetterl, Hason, Tuononen, Silvennoinen, Myller, Cvrcek, Vanek & Prachar, 2008). The effective surface tension, as well as the surface energy related to the topography of surface, is assumed to influence the final interactions of the implant with the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of implanted material becomes immediately (within a few seconds) coated with adsorbed proteins, forming a biofilm, which mediates the interaction between the implant and the environment of the body [8]. Since most implants are exposed to blood during implantation, the initial protein film is mainly composed of blood plasma proteins [9]. After a biofilm is formed, different cells approach the surface, interacting mainly with the adsorbed protein layer.…”
Section: Introductionmentioning
confidence: 99%